Pertangungjawaban Pidana Pemegang Saham pada Tindak Pidana Korporasi dalam Undang-Undang Nomor 1 Tahun 2023 Tentang Kitab Undang-Undang Hukum Pidana (KUHP) - Fransiscus Girsang, Rio; Syahrin, Alvi; Yunara, Edi; Rosmalinda, Rosmalinda (Jurnal Ilmu Hukum, Humaniora dan Politik, 2024)
Corporations have a strategic role in bringing about change and growth in the world economy. Corporations are second only to the State in increasing economic growth and national development, but there are times when corporations also commit various criminal acts that harm the state and society. The damage to banking that occurred in the past was precisely due to the actions of the controlling shareholders of the banks, through the GMS placing people (minions) as members of the board of directors and commissioners. These people who were given strategic positions by the controlling shareholders were puppets of the controlling shareholders and carried out the policies of the controlling shareholders. The case of Bank Harapan Sentosa (BHS) shows how the shareholders had evil intentions by creating a "fictitious" corporation to apply for credit to the bank where the convicted person was the controlling shareholder. The corporate veil doctrine, which provides a veil of protection to shareholders, is considered to be a trigger for the repetition of criminal acts committed by corporations. Law Number 1 Year 2023 on the Criminal Code has been passed. Based on the provisions of Article 613 of the Criminal Code, every legislation, its criminal provisions must refer to Law Number 1 of 2023 concerning the Criminal Code. This research is a normative juridical research that uses a statutory approach, concept approach and case approach. This research uses primary, secondary and tertiary legal materials. The data collection technique used is through literature study where the data collected is grouped according to the problem and then analyzed qualitatively so that conclusions can be drawn. Based on the results of the research, it is known that all arrangements for errors in Law Number 1 of 2023 concerning the Criminal Code can be held accountable to the corporation. Law No. 1 of 2023 on the Criminal Code has regulated the imposition of criminal liability of corporations and shareholders. According to Law No. 1 of 2023 on the Criminal Code, there are 3 (three) roles of shareholders who can be held criminally liable, namely as a person who gives orders, a person who controls and as a beneficial owner of the corporation.